Epidermal growth factor receptor tyrosine kinase inhibitors for non-small cell lung cancer - Asami, Kazuhiro (Baishideng Publishing Group Inc, 2014)
First-generation epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs), including gefitinib and erlotinib, have proven to be highly effective agents for advanced non-small cell lung cancer (NSCLC) in patients harboring an activating EGFR mutation such as the exon 19 deletion mutation and L858R. Although those reversible small molecular targeted agents provide a significant response and survival benefit, all responders eventually acquire resistance. Second-generation EGFR-targeting agents, such as irreversible EGFR/HER2 tyrosine kinase inhibitors and pan-HER TKIs, may improve survival further and be useful for patients who acquired resistance to ﬁrst-generation EGFR-TKIs. This review discusses novel therapeutic strategies for EGFR-mutated advanced NSCLC using first- and second-generation EGFR-TKIs.